Fear of Neighborhood Violence During Adolescence Predicts Development of Obesity a Decade Later: Gender Differences Among African Americans - Assari, Shervin (Arch Trauma Res, 2016)
BACKGROUND: African American youth are more likely than other racial and ethnic groups to be obese. African American youth are also more likely to live in disadvantaged neighborhoods which increase their victimization, observation, and fear of violence. OBJECTIVES: This study tested if victimization, observation, and fear of violence in the neighborhood during adolescence predict trajectory of body mass index (BMI) in the 3rd decade of life in African Americans. PATIENTS AND METHODS: Data came from an 18-year community-based cohort. We used multi-group latent growth curve modeling for data analysis, considering neighborhood violence at age 15 (i.e. victimization, observation, and fear) as predictors, and the linear slope for the average change in BMI from age 21 to 32 as the outcome, with age and socioeconomic status (i.e. intact family and parental employment) as covariates. RESULTS: Fear of neighborhood violence at age 15 was predictive of an increase in BMI from age 21 to 32 among female but not male African Americans. Victimization and observation of violence at age 15 did not predict BMI change from age 21 to 32 among female or male African Americans. CONCLUSIONS: Fear of neighborhood violence is a contributing factor to increased risk of obesity for female African American youth who live in disadvantaged areas. This finding has implications for prevention of obesity among African American women who are at highest risk for obesity in the United States. Initiatives that enhance neighborhood safety are critical strategies for obesity prevention among African American women.